The immune response modulated by inoculation of commensal bacteria at birth impacts the gut microbiota and prevents Salmonella colonization - Kempf, Florent; Drumo, Rosanna; Chaussé, Anne Marie; Menanteau, Pierrette; Kubasova, Tereza; Roche, Sylvie; Lalmanach, Anne Christine; Guabiraba, Rodrigo; Chaumeil, Thierry; Larivière-Gauthier, Guillaume; Caballero-Posadas, Ignacio; Laroche, Béatrice; et al. (Gut microbes, 2025)
Super- and low-shedding phenomena have been observed in genetically homogeneous hosts infected by a single bacterial strain. To decipher the mechanisms underlying these phenotypes, we conducted an experiment with chicks infected with Salmonella Enteritidis in a non-sterile isolator, which prevents bacterial transmission between animals while allowing the development of the gut microbiota. We investigated the impact of four commensal bacteria called Mix4, inoculated at hatching, on chicken systemic immune response and intestinal microbiota composition and functions, before and after Salmonella infection. Our results revealed that these phenotypes were not linked to changes in cell invasion capacity of bacteria during infection. Mix4 inoculation had both short- and long-term effects on immune response and microbiota and promoted the low-shedder phenotype. Kinetic analysis revealed that Mix4 activated immune response from day 4, which modified the microbiota on day 6. This change promotes a more fermentative microbiota, using the aromatic compounds degradation pathway, which inhibited Salmonella colonization by day 11 and beyond. In contrast, control animals exhibited a delayed TNF-driven pro-inflammatory response and developed a microbiota using anaerobic respiration, which facilitates Salmonella colonization and growth. This strategy offers promising opportunities to strengthen the barrier effect against Salmonella and possibly other pathogens.
Keywords: symbióza; kur domácí; Poultry Diseases; microbiota; carrier-state; super-shedder; Chickens; virulence; Salmonella; Bacteria; Gastrointestinal Microbiome; immune response; excretion; salmonelová infekce u zvířat; střevní mikroflóra; nemoci drůbeže; Salmonella Infections, Animal; Animals; zvířata; Symbiosis; Salmonella enteritidis; chicken